Bottled water industry: A quantitative study approach - Francesco Scalamonti (Italian Review of Agricultural Economics (REA), 2021)
This paper is a survey of the Italian bottled water industry that with quantitative approach relates the consumes or operative volumes of mineral water market based on the middle trend of temperatures, the consumed income per-capita and the trend of the population. We present the weight-OLS models for four macro-markets - north western, north eastern, centre, southern - on the data of the Bevitalia survey and the ISTAT-Time Series dataset from 1980 to 2020. The results confirm that the operative volumes depend positively and significantly on itself lagged by one order and the other explicative variables up cited. However, the study not consider other important correlated industries as soft drinks or flavoured waters. In addition, the analysis could be more indepth at the level of regions, provinces and municipalities, or for case-study whit a qualitative approach. In conclusion, the study captures the market dynamics of the industry at long-term, and it brings to the attention of managers, researchers and business economists an industry much important for socio-economic implications and environmental impacts that can cause the consumption of bottled water that policy makers cannot afford to ignore.
Keywords: C51; L10; L66; M21; 330; bottled water; quantitative study; sustainable development